(untitled) (Bangladesh Journal of Medical Science, 2017)
Objective: This ex-vivo study evaluated and compared the canal transportation of the prepared root canals and centering ratio maintained by Mtwo, Protaper and Twited Ni-Ti rotary files using Crown-Down technique. Materials and Method: Thirty non-carious extracted permanent human maxillary central incisors without any fracture and having Vertucci type I canal configuration were selected. The teeth were divided into 3 groups each group comprising of ten teeth. All the teeth were mounted on a wax block and pre instrumented canal CT Scan was performed. Access cavity preparation was done in group samples and canal was prepared using crown down technique by Mtwo, Protaper and Twisted NiTi Rotary file systems for the respective groups. Image analysis was done at 9 levels to access transportation and centricity ratio from pre and post instrumented CT scan images. The results showed that Software program determined the volume of pre and post instrumented canals. Results: The Canal transportation occurred least in root canals prepared by Twisted files, followed by canals prepared by Mtwo files and Protaper files. Centricity ratio was maintained the best in root canals prepared by twisted files. Conclusion: Within the parameters of this study, canals prepared by Twisted Files showed a well centered preparation and maintained the original shape of the root canal without any aberrations. Bangladesh Journal of Medical Science Vol.16(2) 2017 p.212-218